Combining Serum DNA Methylation Biomarkers and Protein Tumor Markers Improved Clinical Sensitivity for Early Detection of Colorectal Cancer - Guoying Zhang; Fang He; Guodong Zhao; Zihui Huang; Xiang Li; Xia Xia; Yidi Guo; Weiping Xu; Shangmin Xiong; Yong Ma; Minxue Zheng; Wanli Liu (International Journal of Genomics)
Background. Colorectal cancer (CRC) is one of the leading causes of cancer deaths worldwide and in China. Early CRC screening is the best approach to reduce its incidence and mortality rates. The ColoDefense test, a multiplex qPCR assay simultaneously detecting both methylated SEPT9 and SDC2 genes, has demonstrated improved clinical performance on either methylation biomarker alone for CRC screening with both blood and stool samples. Method. Leftover blood chemistry test samples from 125 CRC, 35 advanced adenoma, and 35 small polyp patients and 92 healthy control subjects were examined by the ColoDefense test. Among these samples, the levels of three circulating tumor markers, CEA, AFP, and CA19-9, were also measured for 106 CRC, 28 advanced adenoma, and 20 small polyp patients and all control subjects. Results. Due to the smaller volume and extended storage in nonfrozen state, the ColoDefense test with these samples exhibited reduced performance for all stages of CRC and advanced adenomas. The performance of CEA, AFP, and CA19-9 and their various combinations was also evaluated for CRC screening to identify the tumor marker combinations with the best performance. When combined with the ColoDefense test, the identified combinations did improve the clinical performance. Conclusion. These results suggested a rational path towards developing a CRC screening method that takes advantage of leftover blood chemistry test samples. The successful development of such a method will undoubtedly help promote early CRC screening by increasing its accessibility for the general public.